Impact of a pension system and an enterprise on employees’ retirement: an intergenerational context - Chybalski, Filip; Gumola, Małgorzata (Lodz University of Technology Press, 2021)
Thus, the goal of this paper is to identify and characterize main elements of this nexus in the context of retirement decisions taking intergenerational relations into account. We focus on the pension system’s impact (with its main parameter, which is a pensionable age (statutory retirement age)) on the employers’ behaviour, as well as the employers’ (workplace) impact on employees’ retirement decisions (reflected in effective retirement age). The paper is structured as follows. First, we present a pension system in an intergenerational context. Second, we attempt to discuss a pensionable age as a determinant of an enterprise activity in the role of an employer. The subsequent section tackles the issue of the possible impact of the employer on employees’ retirement decisions. The paper ends with a brief summary of issues discussed.
Keywords: pension systems; ageing populations; retirement decisions; pensionable age; employees’ retirement decisions; impact of enterprises on employees’ retirement decisions